Particle velocity of submicron polystyrene latex and bubble formation in aqueous system under continuous and pulsed direct current - Abu Bakar, N.F.; Basaruddin, B.; Naim, M. Nazli; Lenggoro, I. Wuled; Iijima, M.; Kamiya, H. (Springer, 2024)
The factors that affect electrophoretic mobility, namely particle velocity of polystyrene latex (PSL) particles and bubble growth rate on the electrode in the aqueous system were investigated during the continuous and pulsed direct current (DC) of electrophoretic deposition (EPD). The velocity of the PSL particles of varied sizes, i.e., 600, 300 and 100 nm at pH 5.5 and electric field strength of 4.1 V/cm were measured using a zeta potential meter under continuous and pulsed DC frequencies of 83.3, 10 and 5 Hz. The bubbles growth rate on the electrodes under the same condition was duplicated and measured separately using a recorded video attached to a microscope. Pulsed DC showed a more uniform particle velocity between 1.5 and 8 μm/s with a narrower particle velocity distribution than the continuous DC. The velocity of the particles was reduced by approximately 50 of the continuous DC. Pulsed DC also significantly reduced the bubble growth (gas formation) rate by three times lower than the continuous DC with a maximum bubble size of approximately 446 μm. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.